1994
DOI: 10.2134/jpa1994.0086
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spatially Variable Nitrogen Fertilizer Management in Winter Wheat

Abstract: Spatially variable N application may improve N use efficiency, grain yield, and net returns of winter wheat (Triticum aestivum L.) in fields exhibiting wide ranges of soil characteristics. The objectives of this study were to (i) determine the variability in optimal economic grain yield and in the amount of N required to produce a unit of grain at optimum yield, the unit N requirement (UNR), among landscape positions; (ii) evaluate landscape position as a criterion for dividing fields into units of equal produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 16 publications
1
32
0
2
Order By: Relevance
“…Explanation of systematic differences in plant-available N as a function of landscape requires integration of soil properties, N-cycling, previous management and cropping effects (Fiez et al 1994). As a result, complex patterns of net supply and crop uptake may preclude accurate prediction of soil residual nitrate levels, the most agronomically important form of mineral N, in the soil profile.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Explanation of systematic differences in plant-available N as a function of landscape requires integration of soil properties, N-cycling, previous management and cropping effects (Fiez et al 1994). As a result, complex patterns of net supply and crop uptake may preclude accurate prediction of soil residual nitrate levels, the most agronomically important form of mineral N, in the soil profile.…”
mentioning
confidence: 99%
“…Spring residual nitrate concentrations may be spatially random (Mulla 1993), greater in convergent areas (Malo and Worcester 1975), or greater in divergent areas (Farrell et al 1996). Nonetheless, total N concentration and mineralization often increases with organic matter and convergent landscape character (Fiez et al 1994).…”
mentioning
confidence: 99%
“…For SWWW under sample project 1, we assumed that site specific N management could, on average, result in a 25 kg N ha −1 decrease in N fertilizer rate compared to uniform N management without decreasing yield (Mulla et al, 1992;Fiez et al, 1994a;Huggins, 2010;Taylor, 2016). For HRWW and HRSW under sample projects 2 and 3, we assumed that site specific N management could, on average, result in a 10 and 20 kg N ha −1 decrease in N fertilizer rate compared to uniform N management without decreasing yield or grain protein concentration, respectively (Huggins, 2010).…”
Section: Sample Projects 1 Through 3: Switch From Uniform To Variablementioning
confidence: 99%
“…However, variability in wheat yield and N requirement has been observed across agricultural fields within the Palouse region of the iPNW (Mulla et al, 1992;Fiez et al, 1994a,b;Huggins, 2010). For example, Fiez et al (1994a) reported soft white winter wheat grain yield to vary by up to 63% and the UNR to vary by up to 70% in the Palouse. Sowers et al (1994) observed split N applications in winter wheat to produce similar grain yield with 25-40% less N. This indicates that variable rate and/or split N fertilizer application have the potential to reduce overall N rate without decreasing yield.…”
Section: Introductionmentioning
confidence: 99%
“…Esta variação, decorrente da ação de agentes naturais, assim como da ação antrópica, deve se manifestar com maior intensidade em algumas propriedades do que em outras (PRIMAVERA, 1998 A aplicação de fertilizantes em taxa variada, baseada na variabilidade do solo dentro de um campo, tem um potencial para reduzir sub e sobre doses, e assim melhorar a eficiência de uso de fertilizantes, o rendimento das culturas e o lucro líquido da propriedade (FIEZ et al, 1994).…”
Section: Variabilidade Dos Atributos Do Solounclassified